The Role Of The Tourism Office In Developing Likupang Tourism In North Minahasa Regency, North Sulawesi Province - Anita Fransiska Rumbayan; Halilul Khairi; Zubakhrum B. Tjenreng (Sean Institute, 2025)
This study examines the role of the Tourism Office and the obstacles faced in developing Likupang tourism, which is one of the Super Priority Tourism Destinations (DPSP) in Indonesia. The qualitative descriptive research method was used with data collection through documentation, observation, interviews and analyzed using ATLAS.ti software. The results of the study show the role of the Tourism Office including: 1) Coordinating with related parties in the development of Likupang, encouraging community participation in capacity building programs, and developing new attractions; 2) Striving to improve infrastructure for basic needs, including road quality and efforts to provide pioneering Damri transportation for easy access; 3) Improving supporting facilities in the form of health services, security and better telecommunications coverage; 4) Striving to achieve the concept of tourism awareness to create a conducive environment for tourism by organizing environmental cleanliness, sanitation and waste management training; and 5) Developing tourism promotion through participation in national and international events and through the use of social media. Several obstacles were identified, including: 1) Lack of Human Resources of civil servants with educational background in tourism 2) Limited allocation of government budget in tourism development in North Minahasa Regency; 3) Low community involvement in tourism development. This study concludes that the role of the North Minahasa Regency Tourism Office has been quite optimal in striving for Likupang tourism development through the program activities carried out which aim to support Likupang as a DPSP, but adjusted to regional capabilities.